2022
DOI: 10.1038/s41396-022-01314-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial invasion of a toxic medium is facilitated by a resident community but inhibited as the community co-evolves

Abstract: Predicting whether microbial invaders will colonize an environment is critical for managing natural and engineered ecosystems, and controlling infectious disease. Invaders often face competition by resident microbes. But how invasions play out in communities dominated by facilitative interactions is less clear. We previously showed that growth medium toxicity can promote facilitation between four bacterial species, as species that cannot grow alone rely on others to survive. Following the same logic, here we a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Indeed, At evolving alone was the only condition where degradation improved over the course of the experiment and largely surpassed the degradation ability of the community, even though the community includes At . In follow-up experiments reported elsewhere we also found that new, non-resident species were more likely to invade the ancestral compared to the evolved community 44 , suggesting that the community members evolved to cover the available niche space. An alternative initial hypothesis was that positive interactions might increase, leading to the evolution of mutualism (H1 in Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Indeed, At evolving alone was the only condition where degradation improved over the course of the experiment and largely surpassed the degradation ability of the community, even though the community includes At . In follow-up experiments reported elsewhere we also found that new, non-resident species were more likely to invade the ancestral compared to the evolved community 44 , suggesting that the community members evolved to cover the available niche space. An alternative initial hypothesis was that positive interactions might increase, leading to the evolution of mutualism (H1 in Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Over the 44 transfers (Fig. 5A), Ct and the two evolved communities reduced their degradation efficiency, such that at the end, they degraded less than their ancestral counterparts (%COD on day 7, isolates from transfer 1 vs. 44 Knowing that At was a member of the two evolved communities, we wondered why the degradation efficiency of the communities was worse than At evolved alone. Did the community members inhibit the degradation efficiency of At or did it not evolve improved degradation?…”
Section: At Degrades Mwf Better After Evolving Alone But Not In Commu...mentioning
confidence: 99%
“…changes in microbial communities colonizing the surface of microplastics are continuously exchanged with microorganisms in the surrounding water [ 13 , 40 ]. However, as the succession of microbial communities in the plastisphere progresses, resident taxa may occupy more ecological niches and monopolize resource availability in colonized environments, thereby reducing further microbial invasions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of facilitation to community invasion thus depends on a complex interplay between the resident community's existing niche partitions (Wei et al 2015), environmental conditions (Yang et al 2017) and species' specific or evolutionary effects (van der Putten et al 2007, Jousset et al 2013). The effect of facilitation on such emergent properties has remained a pressing unknown in facilitation research for the last two decades (Richardson et al 2000, Stachowicz and Byrnes 2006, Li et al 2018, Piccardi et al 2022).…”
Section: Facilitation's Effect On Emergent Propertiesmentioning
confidence: 99%